Dampak Inklusi Keuangan Terhadap Literasi Keuangan dan Financial Technologi Di IIB Darmajaya - Irawati, Anik; Putra, Dedi; Swissia, Pebrina (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2022)
This study aims to determine the effect of Financial Literacy and Financial Technology on Student Financial Inclusion at IIB Darmajaya. This research is quantitative and the research data used are primary and secondary data. The population in this study were students majoring in Accounting with a concentration in finance. The sampling technique used is the sholving method, in order to obtain 86 students at IIB Darmajaya Accounting Department to be respondents. The analytical method used is descriptive analysis and multiple linear regression analysis. The data was processed statistically with the t test model. The results of this study indicate that the variables of financial literacy and financial technology simultaneously have a significant effect on the financial inclusion of students in North Sumatra. Partially, the variables of financial literacy and financial technology have a positive and significant effect on the financial inclusion of students at IIB Darmajaya.